A Family of Immobilizable Chiral Bis(pinenebipyridine) Ligands - Pöllnitz, Alpár; Skupienski, Radek; Stoeckli-Evans, Helen; Crochet, Aurélien; Silvestru, Anca; Fromm, Katharina M.; Mamula, Olimpia (Synlett, 2013)
New enantiopure ligands containing two (–)-5,6-pinenebipyridine units connected by a bridge situated in position 6′ of the bipyridines have been prepared. The chemically addressable groups of the bridging (hydroxyl or keto) can be covalently bound to various supports in order to heterogenize the ligand.
Keywords: pyridine; chirality; stereoselective synthesis; ketone; alcohol groups